2019
DOI: 10.1017/s1751731118003671
|View full text |Cite
|
Sign up to set email alerts
|

Response of rumen microbiota, and metabolic profiles of rumen fluid, liver and serum of goats to high-grain diets

Abstract: Feeding ruminants a high-grain (HG) diet is a widely used strategy to improve milk yield and cost efficiency. However, it may cause certain metabolic disorders. At present, information about the effects of HG diets on the systemic metabolic profile of goats and the correlation of such diets with rumen bacteria is limited. In the present study, goats were randomly divided into two groups: one was fed the hay diet (hay; n = 5), while the other was fed HG diets (HG; n = 5). On day 50, samples of rumen contents, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
4
20
0
5
Order By: Relevance
“…Previous studies reported that uracil concentration in the rumen was increased with high concentrate diets [63,64], which was consistent with our study. In addition, correlation analysis revealed that uracil was positively correlated with Ruminococcus_2.…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies reported that uracil concentration in the rumen was increased with high concentrate diets [63,64], which was consistent with our study. In addition, correlation analysis revealed that uracil was positively correlated with Ruminococcus_2.…”
Section: Comparison Of the Composition And Differences Of Ruminal Metsupporting
confidence: 93%
“…The increased concentration of uracil in the rumen of SWCG in Group H might re ect that some bacterial nucleic acids were rapidly degraded to uracil by Ruminococcus_2 [65]. 5-oxoproline (pyroglutamic acid) could be the intermediate product in the glutathione cycle and its concertation was negatively correlated with the concentration of antioxidantglutathione [63,66,67]. Based on the correlation analysis, Lachnospiraceae_ND3007_group might decrease the concentration of 5-oxoproline and more glutathione was produced in Group H to promote antioxidative capacity.…”
Section: Comparison Of the Composition And Differences Of Ruminal Metmentioning
confidence: 99%
“…In line with cows, high grain diets reshape the rumen microbial community by reducing its richness and diversity and changing the microbial composition in goats. Zhang et al (2019) showed that 30 taxa were affected by the diet, there being 5 enriched taxa (Selenomonas 1, Ruminococcus and unclassified Veillonellaceae) in the high grain diet group and 25 enriched taxa in the hay diet group (Butyrivibrio, Pseudobutyrivibrio, Fibrobacter and several unclassified taxa such as unclassified Christensenellaceae, Ruminococcaceae and Ruminococcaceae) at the genera level. These changes in the composition of the microbiota were associated with modifications in the rumen metabolome with enhanced capacity to influence amino acid and nucleotide metabolisms.…”
Section: Microbiotamentioning
confidence: 99%
“…Most of the time, it is the association between different complementary approaches which provides most information. For example, by combining metabolomics and proteomic studies, it is possible to get a better knowledge of the role of the rumen epithelium in goats adapted to grain-rich feeding compared to hay feeding (Guo et al, 2019).The joint and simultaneous use of metabolomics and pyrosequencing studies in goats informs about the metabolic pathways preferentially involved in the response to high-grain diets (Zhang et al, 2019), whilst the links between the ruminal bacterial community and metabolites represent a powerful tool in terms of prediction or monitoring of certain nutritional diseases such as acidosis (Mao et al, 2016;Hua et al, 2017). These approaches also make it possible to investigate more finely and specifically via co-culture the key role of microorganisms such as fungi and methanogens, but also the nature of the metabolites produced (Cheng et al, 2013).…”
Section: Omicsmentioning
confidence: 99%
“…Trabalhos como os de Parente et al (2016), Caetano et al (2019) e Oliveira et al (2015a) têm comprovado ganhos na terminação de animais alimentados com dieta contendo alta concentração de grãos e baixa concentração de volumoso, relação 85:15%, respectivamente. Contudo, frequentemente os mecanismos fisiológicos de homeostase são rompidos, ocorrendo redução do pH ruminal, com alterações que podem ser prejudiciais à microbiota do rúmen e deixam o animal mais susceptível a doenças metabólicas e infecciosas (DONG et al, 2013;SEDDIK et al, 2019;ZHANG et al, 2019a).…”
unclassified